Analysis of Corn Cob Briquette Characteristics Using Different Adhesives in the Pyrolysis Process - David Mangallo; Thomas Pagasis; Rombe Allo; Mickael Ruben Kaiway; Enos Tambing; Selyus Rantepulung (Universitas Islam Raden Rahmat, Malang, 2025)
Corn cobs, an abundant agricultural waste, represent a promising alternative energy source when converted into briquettes. This study aimed to characterize corn cob briquettes and determine the optimal adhesive type and concentration for enhanced performance. Charcoal was produced from corn cobs via pyrolysis in repurposed oil drums, then ground and sieved through a 60-mesh screen. The resultant charcoal was combined with either starch or sago starch adhesives at concentrations of 7.5%, 10%, 12.5%, and 15% and subsequently molded into honeycomb briquettes using a 4-inch diameter mold with 16 perforations, fabricated from galvanized iron pipes and operated with a hydraulic jack. Proximate analysis indicated moisture levels of 5.37–6.71%, ash levels of 30.64–39.16%, volatile matter levels of 20.61–23.07%, fixed carbon proportions of 32.53–42.44%, and calorific values between 2893 and 3727 kcal/kg. A Water Boiling Test conducted with 1 liter of water demonstrated that briquettes incorporating 7.5% sago starch adhesive achieved boiling within 36 minutes, indicating superior combustion efficiency. These findings confirm the potential of corn cob briquettes as a renewable energy source and underscore the critical role of adhesive formulation in optimizing biomass fuel performance.